2008
DOI: 10.1017/s026502150700316x
|View full text |Cite
|
Sign up to set email alerts
|

Topical ketamine and morphine for post-tonsillectomy pain

Abstract: Topical ketamine and morphine seems to be a safe and easy analgesic approach for decreasing adenotonsillectomy pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 53 publications
0
39
1
1
Order By: Relevance
“…They reported higher pain scores on arrival in the recovery room in the placebo group. They found morphine and ketamine groups had longer effective analgesia time and reduced analgesic requirement on the first postoperative day than the mixture of morphine plus ketamine and control groups [10].…”
Section: Discussionmentioning
confidence: 98%
“…They reported higher pain scores on arrival in the recovery room in the placebo group. They found morphine and ketamine groups had longer effective analgesia time and reduced analgesic requirement on the first postoperative day than the mixture of morphine plus ketamine and control groups [10].…”
Section: Discussionmentioning
confidence: 98%
“…It has been delivered via the intravenous, intramuscular, rectal, subcutaneous [42], transdermal [43], topical [43], oral [44], intranasal [45], sublingual [46], transmucosal [47,48], epidural, and intrathecal routes. It has been gargled [49], locally infiltrated [50], and used in intravenous regional anesthesia [51].…”
Section: Modes Of Administrationmentioning
confidence: 99%
“…Other studies used ketamine topically after tonsillectomy; the treatment produced an analgesic effect and decreased the need for rescue medication. [14][15][16] Satilmiş et al 12 investigated the efficacy of adding ketamine to local anesthetic agents to increase the duration of regional anesthesia and postoperative analgesia during surgical extraction of third molars. They concluded that the combination of a local anesthetic and sub-anesthetic doses of ketamine can produce good local anesthesia.…”
Section: Discussionmentioning
confidence: 99%